Government funding framework for South African Higher Education Institutions - Styger, A; van Vuuren, G W; Heymans, A (South African Journal of Higher Education, 2016)
Since the early 1950s, only four funding formulae have been used for public funding of higher education institutions in South Africa. From the introduction of the Holloway formula in 1953 to the current New Funding Formula (NFF), implemented in 2004, the underlying factors that determine the base of funding for higher education stayed the same. Some principles, such as weighted stu-dent numbers, changed the calculation of students, but student intake, student output and research output still determine funding. While the basis of funding did not change much, the amounts per unit changed significantly, especially since 2001. Research became the focus of some universities, while others in-creased their student intake in order to generate the maximum amount of in-come from government subsidies. The NFF continues to evolve and managerial staff needs the necessary knowledge on the basics of subsidy to make informed decisions. With the new cycle for enrolment planning being done from 2014 to 2019, knowledge of the NFF is more important than ever.